Comparative Transcriptome Profiling of Gaeumannomyces graminis var. tritici in Wheat Roots in the Absence and Presence of Biocontrol Bacillus velezensis CC09 - Kang, Xingxing; Guo, Yu; Leng, Shuang; Xiao, Lei; Wang, Lanhua; Xue, Yarong; Liu, Changhong (Frontiers in Microbiology, 2019)
This study aimed to explore potential biocontrol mechanisms involved in the interference of antagonistic bacteria with fungal pathogenicity in planta. To do this, we conducted a comparative transcriptomic analysis of the ‘take-all’ pathogenic fungus Gaeumannomyces graminis var. tritici (Ggt), by examining Ggt-infected wheat roots in the presence or absence of the biocontrol agent Bacillus velezensis CC09 (Bv) compared with Ggt grown on potato dextrose agar (PDA) plates. A total of 4134 differentially expressed genes (DEGs) were identified in Ggt-infected wheat roots, while 2011 DEGs were detected in Bv+Ggt-infected roots, relative to the Ggt grown on PDA plates. Moreover, 31 DEGs were identified between wheat roots respectively infected with Ggt and Bv+Ggt, consisting of 29 down-regulated genes coding for potential Ggt pathogenicity factors—e.g., para-nitrobenzyl esterase, cutinase 1, and catalase-3—and two up-regulated genes coding for tyrosinase and a hypothetical protein in the Bv+Ggt-infected roots when compared with the Ggt-infected roots. In particular, the expression of one gene, encoding the ABA3 involved in the production of Ggt’s hormone abscisic acid, was 4.11-fold lower in Ggt-infected roots with Bv than without Bv. This is the first experimental study to analyze the activity of Ggt transcriptomes in wheat roots exposed or not to a biocontrol bacterium. Our results therefore suggest the presence of Bv directly and/or indirectly impairs the pathogenicity of Ggt in wheat roots through complex regulatory mechanisms, such as hyphopodia formation, cell wall hydrolase, expression of a papain inhibitor, among others, all which merit further investigation.